Auricular Electroacupuncture Reduced Inflammation-Related Epilepsy Accompanied by Altered TRPA1, pPKCα, pPKCε, and pERk1/2 Signaling Pathways in Kainic Acid-Treated Rats - Yi-Wen Lin; Ching-Liang Hsieh (Hindawi Limited, 2014)
Background. Inflammation is often considered to play a crucial role in epilepsy by affecting iron status and metabolism. In this study, we investigated the curative effect of auricular acupuncture and somatic acupuncture on kainic acid- (KA-) induced epilepsy in rats. Methods. We established an epileptic seizure model in rats by KA (12 mg, ip). The 2 Hz electroacupuncture (EA) was applied at auricular and applied at Zusanli and Shangjuxu (ST36-ST37) acupoints for 20 min for 3 days/week for 6 weeks beginning on the day following the KA injection. Results. The electrophysiological results indicated that neuron overexcitation occurred in the KA-treated rats. This phenomenon could be reversed among either the auricular EA or ST36-ST37 EA treatment, but not in the sham-control rats. The Western blot results revealed that TRPA1, but not TRPV4, was upregulated by injecting KA and could be attenuated by administering auricular or ST36-ST37 EA, but not in the sham group. In addition, potentiation of TRPA1 was accompanied by increased PKCα and reduced PKCε. Furthermore, pERK1/2, which is indicated in inflammation, was also increased by KA. Furthermore, the aforementioned mechanisms could be reversed by administering auricular EA and could be partially reversed by ST36-ST37 EA. Conclusions. These results indicate a novel mechanism for treating inflammation-associated epilepsy and can be translated into clinical therapy.